Effect of agricultural diversification on dietary diversity in rural households with children under 5 years of age in Zambia - Chewe Nkonde (Wiley, 2021)
Abstract Micronutrient deficiencies in low‐income countries are associated with the monotonous consumption of nutrient‐deficient crops, contributing to childhood stunting with far‐reaching socioeconomic consequences. To promote nutrition sensitive agriculture, policy makers in such countries have embarked on policy initiatives that encourage agricultural diversification in smallholder farming systems. This paper investigates the link between agricultural diversification and two key indicators of food and nutrition security among children under 5 years in rural Zambia. Data from the 2015 Rural Agricultural Livelihoods Survey and regression models are used to explain household dietary diversity and months of inadequate household food provisioning among 7934 households. Factors associated with the key outcome variables include land cultivated, household size, total livestock units, household head education, households receiving extension information, and use of productivity‐enhancing inputs such as fertilizers. Although the results demonstrate that agricultural diversification is positively associated with the household dietary diversity score, the relationship is not statistically significant. Further, the study findings illustrate that agricultural diversity is negatively associated with months of inadequate household food provisioning but that this relationship is also not statistically significant. The implication for policy is that other interventions such as productivity enhancement and behavioral change communication need to be scaled up.